PCR analysis for meat products authenticity - detection of horse meat - Stefanova Petya; Gotcheva Velitchka; Angelov Angel (BIO Web of Conferences, 2023)
Food adulteration regarding species origin of meats is a common problem in the meat products sector. With regard to horse meat, its undeclared use in food products is not only a fraud, but could present a health risk since is often associated with the presence of the veterinary drug phenylbutazone in meat products. Therefore, it is important to use reliable methods for authentication of meat products regarding their species composition, which are applicable to complex food matrices. Polymerase chain reaction (PCR) with species-specific primers remains the most widely used analytical approach to detect species-related food adulteration due to its high sensitivity and specificity. The aim of the present study was to establish the authenticity of 20 different meat products on the Bulgarian market without declared horse meat content by using a species-specific PCR method. The specificity test of the PCR method used showed no amplification of DNA from beef and pork. A detection limit of 0.01% horse DNA in three-component meat mixtures was established for the PCR method. The PCR method enabled detection of undeclared presence of horse meat in 25% of the analyzed meat products, which demonstrates the need for strict control regarding authenticity in the meat food chain.